2010
DOI: 10.1111/j.1439-0272.2009.01033.x
|View full text |Cite
|
Sign up to set email alerts
|

Eradication of Chlamydia trachomatis parallels symptom regression in chronic bacterial prostatitis patients treated with a fluoroquinolone-macrolide combination

Abstract: To investigate the association between eradication of Chlamydia trachomatis (CT) and symptom regression in chronic prostatitis, 55 symptomatic patients were subjected to segmented tests to localise CT in first voided urine (VB1), prostatic secretions (EPS), post-massage voided (VB3) or semen specimens. Patients were divided in three treatment groups: the 'urethral involvement' group ('U': VB1 positive, EPS/VB3/Semen negative) was treated with 500 mg day(-1) azithromycin for 3 days. The 'prostatitis' group ('P'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 29 publications
0
10
0
1
Order By: Relevance
“…Microbiological eradication rates were 40-77% for ciprofloxacin [65][66][67], 75% for levofloxacin [65], 80% for azithromycin [66,68,69], 77% for doxycycline [68], 80% for clarithromycin [69], and 62-77% for azithromycin + ciprofloxacin (depending on ciprofloxacin dose) [70]. Higher eradication rates (>90%) were reported with azithromycin and levofloxacin either alone, in combination or sequentially, depending on the locality of infection (urethral, prostatic or both) in patients with CBP with C. trachomatis infection [71]. Significant differences in symptom severity, as assessed by changes in NIH-CPSI scores, were seen between baseline and the end of treatment in two trials [70,71].…”
Section: A-adrenergic Antagonistsmentioning
confidence: 88%
See 1 more Smart Citation
“…Microbiological eradication rates were 40-77% for ciprofloxacin [65][66][67], 75% for levofloxacin [65], 80% for azithromycin [66,68,69], 77% for doxycycline [68], 80% for clarithromycin [69], and 62-77% for azithromycin + ciprofloxacin (depending on ciprofloxacin dose) [70]. Higher eradication rates (>90%) were reported with azithromycin and levofloxacin either alone, in combination or sequentially, depending on the locality of infection (urethral, prostatic or both) in patients with CBP with C. trachomatis infection [71]. Significant differences in symptom severity, as assessed by changes in NIH-CPSI scores, were seen between baseline and the end of treatment in two trials [70,71].…”
Section: A-adrenergic Antagonistsmentioning
confidence: 88%
“…Higher eradication rates (>90%) were reported with azithromycin and levofloxacin either alone, in combination or sequentially, depending on the locality of infection (urethral, prostatic or both) in patients with CBP with C. trachomatis infection [71]. Significant differences in symptom severity, as assessed by changes in NIH-CPSI scores, were seen between baseline and the end of treatment in two trials [70,71]. Others reported improvements in clinical outcomes but failed to use validated tools to report these [65][66][67][68][69] Of the identified comparative studies in patients with CBP, one (n = 408) found that levofloxacin offered advantages over ciprofloxacin for bacterial eradication rates and clinical improvement [67], while another of similar size (n = 377) and design showed no significant differences between these agents [65].…”
Section: A-adrenergic Antagonistsmentioning
confidence: 99%
“…Blacklock et al [31], noted that some patients with CP / CPPS had some pathogens identified in vaginal cultures of their sexual partners. Magri et al [32], evaluated 55 symptomatic patients with CP / CPPS they were subjected to segmented tests to localise Chlamydia trachomatis in first voided urine (VB1), prostatic secretions (EPS), post-massage voided (VB3) or semen specimens. Patients were divided in three treatment groups: the 'urethral involvement' group (VB1 positive, EPS/VB3/Semen negative) was treated with 500 mg day(-1) azithromycin for 3 days.…”
Section: Pathogenesismentioning
confidence: 99%
“…Results of recent observational studies show that therapy based on the combination of azithromycin and levofloxacin is characterized by high eradication (94%) and low relapse rates (77).…”
Section: Clinical Evidence Of Efficacy Of Macrolides In Prostate Infementioning
confidence: 99%